Kualitas Perairan Sungai Buaya di Pulau Bunyu Kalimantan Utara pada Kondisi Pasang Surut - Bambang Kurniadi; Sigid Hariyadi; Enan Mulyana Adiwilaga (Institut Pertanian Bogor, 2015)
Buaya River is one of the river in Bunyu Island which is found near with domestic and agricultural activities. Moreover, Buaya River is also used for fisheries activity by people nearby (fish products collecting and processing) and also used by the fisherman as the back of the boat. These activities will influence and change water quality. This research aimed to analysed water quality condition at Buaya River. Water quality assessment was conducted at four observation station. Water quality was analysed using Storet index and was compared with threshold for marine organisms (Kepmen No. 51/MENLH/2004). The result showed that Buaya River had been polluted at medium level at tide and medium to heavy level at low tide. TSS, oil and grease were not suitable with marine organisms threshold at all stations in low high and low tide.